Effectiveness of a brief intervention with and without booster session for adolescents hospitalized due to alcohol intoxication. (2nd January 2016) - Wurdak, Mara; Kuntsche, Emmanuel; Kraus, Ludwig; Wolstein, Jörg
Abstract: Background : The Hart-am-LimiT (HaLT) project is a brief intervention program for adolescents hospitalized due to alcohol intoxication in Germany. Objective : To test whether a booster session has an impact on participants' drinking behavior compared with the standard HaLT program. Methods : On the morning after their admission due to alcohol intoxication, 411 adolescents in the Federal State of Bavaria were interviewed between October 2008 and January 2010 and socio-demographic data and information on previous drinking behavior were recorded ( t 1). Eleven to 25 months ( M  = 16.4) after their hospital treatment, 106 adolescents completed an online questionnaire ( t 2). Results : Subgroup analysis (ANOVA with repeated measurements) indicated that adolescents who took part in the booster session did not increase episodic heavy drinking (EHD; t 1: M  = 1.68 EHD d; t 2: 1.59 EHD d) in contrast to the non-participating group ( t 1: M  = 1.08 d EHD; t 2: 2.66 d EHD; F  = 4.383, p  = 0.039). Conclusion : Considering the study's limitations (e.g. no randomization, low response rate, etc.), the results indicate a positive effect of a booster session following a brief intervention for adolescents who have been treated in hospital due to alcohol intoxication. Adolescents should therefore be motivated and encouraged to participate in booster sessions.